Faktor-faktor yang mempengaruhi pengangguran dan dampaknya terhadap kemiskinan di Provinsi Jambi - Apriyanti, Ade suci; Hidayat, Syurya; Zulfanetti, Zulfanetti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to analyze the development of unemployment, poverty, HDI, economic growth, investment, and UMP in Jambi Province, to analyze the influence of HDI, economic growth, investment, and UMP factors on unemployment in Jambi Province, to analyze the relationship between unemployment and poverty in Jambi Province. The data used in this study is secondary data with the type of Time series 2000-2019 data in Jambi Province, research data originating from the Central Statistics Agency. This study uses multiple regression analysis and correlation and uses the SPSS tool. The effect of the human development index, economic growth, investment and the provincial minimum wage on unemployment in the province is concluded by the human development index, economic growth, investment and provincial minimum wage on unemployment in Jambi Province with an R2 of 80.7 percent. Based on the test, it can be seen that the correlation value between unemployment and poverty has a strong relationship with the correlation coefficient value of 0.767 with a positive and significant direction (0.045 <0.05).